Análise das propriedades mecânicas de materiais favos de mel em configurações de diamante e cruz: uma abordagem com base na teoria de pórticos planos - Gomes, Rainara Souza (2024)
Honeycomb materials, also known as cellular materials or honeycomb materials, are applied in various areas, such as architecture, engineering and biomedicine. In civil engineering, these materials are used as structural reinforcement, geotechnical solutions or in sandwich structures. The mechanical properties of these materials are intrinsically influenced by the unit cell configurations. Research in this area has grown in recent decades, focusing on mechanical behaviors, which can have isotropic or anisotropic characteristics. The present study aims to investigate the mechanical properties of in-plane cellular materials, focusing on diamond and cross-shaped unit cell configurations. To achieve this objective, the concepts of the theory of flat frames are used as a methodological basis, based on the law of elasticity and plasticity via Timoshenko's flexural theory. In this research, the elastic and plastic properties of honeycombs in diamond and cross configurations are analyzed, using a failure criterion. The results are validated by comparing the efforts and displacements calculated for two-dimensional media composed of finite elements of flat frames, with constituent material properties, and quadrilateral finite elements, with the effective properties of the unit cell. These results proved that the methodology adopted satisfactorily describes the behavior of honeycomb materials in cross and diamond configurations. In particular, the elastoplastic approach for the cross configuration was compared with experiments with satisfactory accuracy.